The Hydration-Induced Ca2+ Release Is a General Phenomenon in Characeae - Shimada, Kiyo; Kikuyama, Munehiro; Tazawa, Masashi (Oxford University Press, 1996)
When an internodal cell of Nitella axilliformis that had been treated with 10 mM KCl and 1 mM EGTA was examined for transcellular osmosis, an increase in the cytosolic concentration of Ca2+ on the endoosmotic side was observed, as was the case in Nitella flexilis even though the increase was much smaller in Nitella axilliformis . The hydration-induced calcium release (HICR) was also observed in other species of Characeae, namely, Chara corallina and Nitellopsis obtusa . HICR was also demonstrated in cytoplasm isolated from Nitella axilliformis and Chara corallina as from Nitella flexilis . Thus, it appears that HICR is not specific to Nitella flexilis but may be a general phenomenon in Characeae.